N 2 O changes from the Last Glacial Maximum to the preindustrial – Part II: Terrestrial N 2 O emissions constrain carbon-nitrogen interactions - Joos,F; Spahni,R; Stocker,BD; Lienert,S; Müller,J; Fischer,H; Schmitt,J; Prentice,IC; Otto-Bliesner,B; Liu,Z (2019)
Abstract. Land ecosystems currently take up a quarter of the human-caused carbon dioxide emissions. Future projections of this carbon sink are strikingly divergent, leading to major uncertainties in projected global warming. This situation partly reflects our insufficient understanding of carbon-nitrogen (C-N) interactions and particularly of the controls on biological N fixation (BNF). It is difficult to infer ecosystem responses for century time scales, relevant for global warming, from the comparatively short instrumental records and laboratory or field experiments. Here we analyse terrestrial emissions of nitrous oxide (N2O) over the past 21,000 years as reconstructed from ice-core isotopic data and presented in part I of this study. Changing N2O emissions are interpreted to reflect changes in ecosystem N loss, plant available N, and BNF. The ice-core data reveal a 40 % increase in N2O emissions over the deglaciation, suggestive of a highly dynamic global N cycle whereby sources of plant-available N adjust to meet plant N demand and loss fluxes. Remarkably, the increase occurred in two steps, each realized within maximum two centuries, at the onsets of the northern hemisphere warming events around 14,600 and 11,700 years ago. We applied the LPX-Bern dynamic global vegetation model in deglacial simulations forced with Earth System Model climate data to investigate N2O emission patterns, mechanisms, and C-N coupling. The reconstructed increase in terrestrial emissions is broadly reproduced by the model, given the assumption that BNF positively responds to increasing N demand by plants. In contrast, assuming time- and demand-independent levels of BNF in the model to mimic progressive N limitation of plant growth results in N2O emissions that are incompatible with the reconstruction. Our results suggest the existence of (a) strong biological controls on ecosystem N acquisition, and (b) flexibility in the coupling of the C and N cycles during per